INNOVATION IN EARLY CHILDHOOD LEARNING MEDIA: CREATING SPIN GAMES TO IDENTIFY GENDER IDENTITY - Haryanti, Dwi; Withasari, Yurinda; Faruq, Asrul (Universitas Labuhanbatu, 2026)
Purpose-Gender identity formation is tightly linked to early childhood social and emotional development. Nonetheless, traditional approaches that lack interest continue to dominate learning activities for kids aged 4 to 5. The purpose of this project is to create and assess the viability of using Spin Game media as a cutting-edge teaching tool to introduce gender identification to youngsters between the ages of four and five.Methodology-The ADDIE model, comprising analysis, design, development, implementation, and evaluation, was used in this study's Research and Development (R&D) methodology. At PAUD KB Mutiara Bangsa, information was gathered by surveys, observations, and documentation. Teacher response questionnaires, observation sheets measuring children's gender identity recognition, and media and material feasibility questionnaires made up the research tools.Findings-According to the findings, the Spin Game media received a very feasible score of 96.7% from media professionals and 100% from material specialists. 84.4% of children's gender identity recognition was supported, according to observation results from small-scale experiments. Additionally, with a feasibility percentage of 97.3%, teacher replies showed a very high degree of acceptance. These results show that the Spin Game media is efficient and successful for teaching young children.Contribution-By offering a fun, play-based learning tool that promotes gender identity awareness among kids ages 4-5, this study advances early childhood education. The Spin Game enhances the development of learning media for early childhood gender education and provides a practical, creative alternative to conventional teaching techniques.